Peningkatan Aktivitas dan Kemampuan Berfikir Kritis Peserta Didik Melalui Model Pembelajaran Kooperatif Tipe Numbered Heads Together Berbantuan Media Quipper School Di Kelas X Multimedia SMK - Wiwi Oktriani; Ahmad Fauzan; Ellizar Ellizar (International Conferences on Educational, Social Sciences and Technology)
Classroom Action Research through the NHT-aided model of Quipper School media aims to enhance learning activities and critical thinking skills of learners. The subjects of this study are students often grade student. This study was conducted in 2 cycles. there is an increase in student activity during the learning process that is 38% I cycle, and on the II cycle 71%. Based on the cycles test carried out the critical thinking ability of learners also increased from 40% in the first cycle to 80% in cycle II. The result of the research shows the increase of learning activity and critical thinking ability of the students from cycle I to cycle II. From the research result, it can be concluded that the cooperative model of Numbered Heads Together type media quipper school is effective in increasing the activity and critical thinking ability of the students of ten grade student Lesson Year 2016/2017.